Porphyridium purpureum microalga physiological and ultrastructural changes under copper intoxication. (2021) - Markina, Zhanna V.; Orlova, Tatyana Yu.; Vasyanovich, Yuri A.; Vardavas, Alexander I.; Stivaktakis, Polychronis D.; Vardavas, Constantine I.; Kokkinakis, Manolis N.; Rezaee, Ramin; Ozcagli, Eren; Golokhvast, Kirill S.
Graphical abstract: Highlights: The number of cells did not differ significantly at Cu 50 and 100 μg/L compared to the control, whereas Cu 150 μg/L inhibited population growth. The fluorescence of chlorophyll a increased following exposure to Cu 100 μg/L and fluorescence of phycoerythrin enhanced by Cu 150 μg/L. The content of ROS increased with increasing Cu concentration in a dose-dependent manner. The population size structure was also changed by Cu as the number of cells sized 4−6 μm increased in the presence of Cu, especially with Cu 150 μg/L. Abstract: The present work assessed the effect of copper (Cu) on cell dynamics and structure of the microalga Porphyridium purpureum (Rhodophyta, Bangiophycidae). Ultrastructure of the microalga was investigated and fluorescence of chlorophyll a and phycoerythrin, and content of reactive oxygen species (ROS) were estimated by flow cytometry. The number of cells did not show statistically significant differences at concentrations of 50 and 100 μg/L of Cu compared to the control, whereas 150 μg/L of Cu inhibited population growth. The fluorescence of chlorophyll a increased following exposure to Cu 100 μg/L and fluorescence of phycoerythrin enhanced by Cu 150 μg/L. There was no alteration in the above indicators at other concentrations. The content of ROS increased with increasing Cu concentration in a dose-dependent manner. The population size structure was also changed by Cu as the number of cells sized 4–6 μm was increased in the presence of Cu, especially with Cu 150 μg/L. Changes in the topography of thylakoids grew larger with Cu concentration.